Large infrared nonlinear optical response of C60. - BLAU, WERNER (My University, 1991)
C60 buckminsterfullerene exhibits a large ultrafast third-order nonlinear optical response. Degenerate four-wave-mixing measurements in C60-benzene solutions were performed using 50-psec pulses at l.064Itm.The magnitude of the nonlinear susceptibility per C60 molecule is \y\=1.5x1O-42 m5 V-2 andof the same size as that observed in polydiacetylene. In contrast to conjugated polymers, however,a dominant positive real part of the nonlinearity is found, 3 times larger than the imaginary component. The nonlinear response can be described within the model of a free electron in a spherical box, confirming the complete delocalization of electrons on the C60 molecule
PUBLISHED
Keywords: Physics